Hubungan Tingkat Kecemasan Ibu Hamil dengan Keikutsertaan Vaksinasi Covid-19 - Aryani, Hening Ryan; Permatasari, Widy Arum; Wildan, Moh. (Malang Journal of Midwifery (MAJORY), 2022)
One of the efforts to minimize the risk of exposure to COVID-19 in pregnant women is through COVID-19 vaccination. Even though vaccines for pregnant women have been recommended, there are still pregnant women who have not been vaccinated because of the post-vaccination effects and anxiety. The research objective was to determine the relationship between the anxiety level of pregnant women and their participation in the COVID-19 vaccination. The research design was quantitative with correlational analytic methods. A cross sectional approach was carried out on 42 pregnant women based on a purposive sampling technique. The instrument used was a modified Perinatal Anxiety Screening Scale (PASS) questionnaire. The research was conducted in March-May 2022. Data were analyzed using the chi-square test. The results showed that 17 out of 32 pregnant women (40.47%) who took the Covid-19 vaccine did not experience anxiety. Of the 10 pregnant women who did not participate in the vaccination, 8 (19%) experienced severe anxiety and 2 (4.8%) mild/moderate anxiety. The statistical test showed a ?value (<0.001) with a C value of 0.60, so it can be concluded that there is a significant relationship between the anxiety level of pregnant women and participation in the COVID-19 vaccine with a high relationship between the two variables. Pregnant women are expected to search more information about the COVID-19 vaccine so that their anxiety about the vaccine can be resolved. Health workers can participate in approaching and involving families in educational efforts about the importance of vaccination.